United States national interests in a changing world - Nuechterlein, Donald E., 1925-2022 (University Press of Kentucky, 1973)
Although the term national interest has long been used in reference to the foreign policy goals of nations, there has been no generally agreed upon definition of the concept; as a result, Donald E. Nuechterlein contends, there has been a tendency for foreign policy to be determined by institutional prejudice and past policy rather than by a systematic assessment of national interests. By what criterion does a President decide that a given interest is or is not vital-that is, whether he must contemplate defending it by force if other measures fail?In this study Nuechterlein offers a new concep.